PERANCANGAN PLTS ATAP DI KAMPUS SEKOLAH TINGGI ILMU EKONOMI WIDYA GAMA LUMAJANG - Bimas Permada, Krisda; Setiawan, I Nyoman; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2022)
Rooftop solar power plant is energy that utilizes solar energy as an energy source which is then converted into electrical energy as well as an alternative to environmentally friendly electricity generation. Rooftop solar power plants can be installed on the roofs of large buildings,the roof of the STIE Widya Gama campus with an area of 2698.4 m2. Rooftop solar power plant aims as an additional power supply to supply electrical power to the Sekolah Tinggi Ilmu Ekonomi Widya Gama Lumajang campus of 53 kVA installed power on transformer 1. The design of a rooftop solar power plant at the STIE Widya Gama Lumajang Campus uses 100 solar modules of type Vertex TSM-DE18M(II) 500 Wp. Inverter with a capacity of 53 kVA as much as 1 unit type SUNNY TRIPOWER CORE1. solar power plants produce electrical energy of 82322,2 kWh/year to supply the load on STIE Widya Gama Lumajang. Initial investment capital of Rp. 567.005.500 maintenance and operation costs of 1% of the investment capital cost of Rp. 5.670.055 and payback periode for 14 years 6 months if inflation in Indonesia is 4.25%.